Dose predictions for [177Lu]Lu-DOTA-panitumumab F(ab')2 in NRG mice with HNSCC patient-derived tumour xenografts based on [64Cu]Cu-DOTA-panitumumab F(ab')2 - implications for a PET theranostic strategy - Anthony Ku; Misaki Kondo; Zhongli Cai; Jalna Meens; Min Rong Li; Laurie Ailles; Raymond M. Reilly (SpringerOpen, 2021)
Abstract Background Epidermal growth factor receptors (EGFR) are overexpressed on many head and neck squamous cell carcinoma (HNSCC). Radioimmunotherapy (RIT) with F(ab')2 of the anti-EGFR monoclonal antibody panitumumab labeled with the β-particle emitter, 177Lu may be a promising treatment for HNSCC. Our aim was to assess the feasibility of a theranostic strategy that combines positron emission tomography (PET) with [64Cu]Cu-DOTA-panitumumab F(ab')2 to image HNSCC and predict the radiation equivalent doses to the tumour and normal organs from RIT with [177Lu]Lu-DOTA-panitumumab F(ab')2. Results Panitumumab F(ab')2 were conjugated to DOTA and complexed to 64Cu or 177Lu in high radiochemical purity (95.6 ± 2.1% and 96.7 ± 3.5%, respectively) and exhibited high affinity EGFR binding (Kd = 2.9 ± 0.7 × 10− 9 mol/L). Biodistribution (BOD) studies at 6, 24 or 48 h post-injection (p.i.) of [64Cu]Cu-DOTA-panitumumab F(ab')2 (5.5-14.0 MBq; 50 μg) or [177Lu]Lu-DOTA-panitumumab F(ab')2 (6.5 MBq; 50 μg) in NRG mice with s.c. HNSCC patient-derived xenografts (PDX) overall showed no significant differences in tumour uptake but modest differences in normal organ uptake were noted at certain time points. Tumours were imaged by microPET/CT with [64Cu]Cu-DOTA-panitumumab F(ab')2 or microSPECT/CT with [177Lu]Lu-DOTA-panitumumab F(ab')2 but not with irrelevant [177Lu]Lu-DOTA-trastuzumab F(ab')2. Tumour uptake at 24 h p.i. of [64Cu]Cu-DOTA-panitumumab F(ab')2 [14.9 ± 1.1% injected dose/gram (%ID/g) and [177Lu]Lu-DOTA-panitumumab F(ab')2 (18.0 ± 0.4%ID/g) were significantly higher (P < 0.05) than [177Lu]Lu-DOTA-trastuzumab F(ab')2 (2.6 ± 0.5%ID/g), demonstrating EGFR-mediated tumour uptake. There were no significant differences in the radiation equivalent doses in the tumour and most normal organs estimated for [177Lu]Lu-DOTA-panitumumab F(ab')2 based on the BOD of [64Cu]Cu-DOTA-panitumumab F(ab')2 compared to those estimated directly from the BOD of [177Lu]Lu-DOTA-panitumumab F(ab')2 except for the liver and whole body which were modestly underestimated by [64Cu]Cu-DOTA-panitumumab F(ab')2. Region-of-interest (ROI) analysis of microPET/CT images provided dose estimates for the tumour and liver that were not significantly different for the two radioimmunoconjugates. Human doses from administration of [177Lu]Lu-DOTA-panitumumab F(ab')2 predicted that a 2 cm diameter HNSCC tumour in a patient would receive 1.1-1.5 mSv/MBq and the whole body dose would be 0.15-0.22 mSv/MBq. Conclusion A PET theranostic strategy combining [64Cu]Cu-DOTA-panitumumab F(ab')2 to image HNSCC tumours and predict the equivalent radiation doses in the tumour and normal organs from RIT with [177Lu]Lu-DOTA-panitumumab F(ab')2 is feasible. RIT with [177Lu]Lu-DOTA-panitumumab F(ab')2 may be a promising approach to treatment of HNSCC due to frequent overexpression of EGFR.